ANTIINFLAMMATION AND ANTIFUNGAL EFFECTS OF SILVER NANOPARTICLES GREENLY SYNTHESIZED USING PHYLLANTHUS EMBLICA L. EXTRACT AS A REDUCING AGENT AGAINST DERMATOPHYTOSIS - MASFRIA; SUMAIYAH; SYAHPUTRA, HAFID; FANI, VERENTIO (International Journal of Applied Pharmaceutics, 2024)
Objective: This research aims to determine whether the extract of Phyllanthus emblica can synthesize silver nanoparticles as an alternative bioreductive synthesis that is safer and free of hazardous waste. Silver nanoparticles were tested for their anti-inflammatory and antifungal activity on Trichophyton mentagrophytes and Microsporum canis. Methods: This study makes ethanol extract of Phyllanthus emblica fruit, synthesizes silver nanoparticles utilizing green synthesis, and then characterizes and tests for anti-inflammatory and antifungal activities. Results: This research shows that Phyllanthus emblica ethanol extract can be used to produce silver nanoparticles with characterization using a UV-Vis spectrophotometer at 430 nm, and FTIR shows specific wave numbers at 3739, 1703, 1347, 1054 and 875 cm-1. Particle Size Analyzer (PSA) and Scanning Electron Microscope (SEM) analysis of silver nanoparticles showed a colloid size of 25.93 nm and dry silver nanoparticle powder of 112.68 nm with spherical particles and nanometer scale size. In anti-inflammatory activity with a weak IC50 and optimal antifungal activity was seen at concentrations of Trichophyton mentagrophytes (125 mg/ml) and Microsporum canis (150 mg/ml). Conclusion: The ethanol extract of Phyllanthus emblica fruit produced silver nanoparticles with anti-inflammatory and antifungal properties.